Has the Push for Equal Gender Representation Changed the Role of Women on German Supervisory Boards? - Viktor Bozhinov; Christopher Koch; Thorsten Schank (Institute of Labor Economics (IZA), 2017)
In Germany, an intensive public debate about increasing female participation in leadership positions started in 2009 and proceeded until the beginning of 2015, when the German parliament enacted a board gender quota. In that period, the share of women on supervisory boards for 111 German publicly listed and fully codetermined companies (i.e. those which are affected by the quota law) more than doubled from 10.6 percent in 2009 to 22.6 percent in 2015. In 2016, the first year when the law was effective, the female share increased again by 4.5 percentage points. Using a hand-collected dataset, we investigate whether the rise in female board representation was accompanied by a change in gender differences in board member characteristics and board involvement. We do not find evidence for the "Golden Skirts" phenomenon, i.e., the rise in the female share was not achieved via a few female directors holding multiple board memberships. After controlling for firm heterogeneity, the remuneration of female shareholder (employee) representatives is about 16 (9) percent lower than for males. We interpret this as an overall indication that women are not only underrepresented in German supervisory boards, they are even more underrepresented in important board positions. Indeed, women are less likely to become a chairman and are less often assigned to board committees (except for the nominating committee). Moreover, in 2016 the disadvantage of women (as compared to men) to obtain a committee membership is even larger than in 2009.
Keywords: G34; G38; J16; J30; 330; gender diversity; women on boards; gender quota; board remuneration; committee membership